Pemanfaatan energi terbarukan untuk perancangan sistem rotary dryer pada tahap pengeringan daun teh hijau di Kulonprogo - Evrita Lusiana Utari (Faculty of Industrial Technology Universitas Islam Indonesia, 2018)
Indonesia receives solar energy with an average daily energy radiation per unit area per unit time of approximately 4.8 kilowatts / m2. Solar energy is one of the abundant, pollution-free, renewable energy sources and can be explored optimally. In the use of solar energy, it is necessary to develop a technology that is able to convert solar energy into the desired energy, namely electricity. The supply of electrical energy during the day can still be controlled by the solar cell, while at night it is controlled by a battery of 3600 mAH. This technology is known as solar cell or in the international world better known as solar cell or photovoltaic. Solar cell is a tool to convert solar energy into electrical energy. Photovoltaic is a technology that functions to convert or convert solar radiation into electrical energy directly. Rotary dryer is a dryer which is shaped as a drum and rotates continuously which is heated by a heater. A rotary dryer consists of a rotating cylinder and is used to reduce or minimize moisture in the contents of the material and its handling is direct contact with the heat in the drying chamber. The design of the rotary dryer system for the drying process of tea leaves requires a setting temperature of 90oC with a drying time of 15-25 minutes. The energy needed to supply power in the rotary dryer is 1000 WH.